Neighbourhood physical environment influences on children’s outdoor play: a systematic review - Zhao, Xin; Hussain, Norhuzailin; Shukor, Shureen Faris Abdul; Ning, Ji (Frontiers in Built Environment, 2023)
This study conducted a systematic review of 55 studies examining the link between the physical settings in neighbourhoods and children's outdoor play. Scopus databases provide a complete list of journal articles based on stringent inclusion and exclusion standards. Identify the gaps by categorising the significant themes and aspects influencing children's play area requirements. Studies show that the physical environment of a neighbourhood is affected by several social factors besides the needs and preferences of children's games. It was also found that the most commonly used research methods in children's play spaces were survey and interview, and the Affordance Theory was widely used as a research framework. This research provides new design possibilities for children's play areas in residential neighbourhoods. These guidelines emphasise games with varied spatial qualities, the integration of spatial functions, the additional support requirements of parents for children's play, and the flexibility of children to utilise outside space. Consequently, this analysis identifies knowledge gaps and suggests research directions for future studies.